2012
DOI: 10.1007/s10661-012-2883-7
|View full text |Cite
|
Sign up to set email alerts
|

Geochemistry of the suspended sediment in the estuaries of the Mandovi and Zuari rivers, central west coast of India

Abstract: The geochemistry of the suspended particulate matter (SPM) collected during the monsoon was determined to identify the sources of SPM and to understand the physicochemical processes in the Mandovi and Zuari river estuaries. The concentrations of SPM decrease seaward in both estuaries, but are relatively high at bay stations. Kaolinite is the most dominant clay mineral in the upstream of both rivers. Smectite increases seaward in both estuaries and is abundant in the bay. Upstream stations of Mandovi, where ore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(11 citation statements)
references
References 58 publications
1
10
0
Order By: Relevance
“…These compare to more negative values of −27.2 to −30.6 ‰ found in suspended particulate organic matter (SPOM) from upriver sites on the Zuari and Mandovi rivers (Table 1). These values in turn are in line with previous studies which showed SPOM δ 13 C org values ranging from ∼ −21 towards the mouths to ∼ −32 ‰ towards the upstream ends of the estuaries, with values varying with season/discharge and tidal stage (Maya et al, 2011;Khodse and Bhosle, 2012;Kessarkar et al, 2003). Like these SPOM data, the results of the present study therefore indicate mixed OM inputs to sediments across the Zuari and Mandovi estuaries, with varying proportions of marine and terrigenous OM.…”
Section: Organic Matter Sourcessupporting
confidence: 92%
“…These compare to more negative values of −27.2 to −30.6 ‰ found in suspended particulate organic matter (SPOM) from upriver sites on the Zuari and Mandovi rivers (Table 1). These values in turn are in line with previous studies which showed SPOM δ 13 C org values ranging from ∼ −21 towards the mouths to ∼ −32 ‰ towards the upstream ends of the estuaries, with values varying with season/discharge and tidal stage (Maya et al, 2011;Khodse and Bhosle, 2012;Kessarkar et al, 2003). Like these SPOM data, the results of the present study therefore indicate mixed OM inputs to sediments across the Zuari and Mandovi estuaries, with varying proportions of marine and terrigenous OM.…”
Section: Organic Matter Sourcessupporting
confidence: 92%
“…42 Goethite, gibbsite, and kaolinite are typically found in tropical environments due to the intense chemical weathering caused by rain, drainage and topography. 11 These factors favour the hydrolysis process and the leaching of several ions, such as Na, K, Ca, Mg and Sr, which are easily exported to the topographically lower regions and release smaller ions, such as Al, Ti, Si and Fe, that favour the formation of clay minerals. The presence of goethite in association with kaolinite is also influenced by laterite weathering of the Barreiras Formation, which is abundant in the SEPAPM region.…”
Section: Resultsmentioning
confidence: 99%
“…89 In this case, the use of natural and soluble phosphates may contribute to the introduction of Cd, Cu, Cr, Ni, Pb and Zn; 90 nitrogen fertilisers and limestone contribute approximately 1% Cu and Pb, and pesticides affect the contents of As, Cu and Zn. 91 The comparison between the concentrations of the analysed chemical species indicates that the SEPAPM has similar or lower concentrations than other estuarine regions, [6][7][8][9][10][11] which suggests that the natural influences are generally more significant than the anthropic contributions. The interactions between chemical species and salinity, OM, pH and oxides are also important, as has been observed in other estuarine environments.…”
Section: Metals and Arsenic Associated With Spmmentioning
confidence: 99%
See 1 more Smart Citation
“…Distribution and characteristics of metal concentrations and consequently the sediment quality of the Subarnarekha river indicated inputs from anthropogenic activity as well as geogenic sources. Kessarkar et al (2013) studied the geochemistry of the suspended sediment to identify the sources of SPM and to understand the physicochemical processes in the Mandovi and Zuari river estuaries. They found that canal stations exhibited the highest concentrations of major and trace metals.…”
Section: Environmental Sediment Geochemistrymentioning
confidence: 99%